Post a New Question


posted by .

How do I solve:
log6 (x^2-5x) = 1

1/2log5(r-2)-log5 r)

log2 (x-1/x^8)

I really don't know how to do these or even start

  • Math (#1 of 3) -

    I assume the number immediately after log is the base of the log.

    log6 (x^2-5x) = 1 is equivalent to writing
    6^1 = x^2-5x = 6
    Rewrite as a polynomial
    x^2 -5x -6 = 0
    (x-6)(x+1) = 0
    x = 6 or -1

    Do the others the same way. Rewrite the equation containing the log term as a polynomial, and factor it.

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question